2015
DOI: 10.4103/2231-0746.175757
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of parotid gland (malignant mixed tumor)

Abstract: Salivary gland carcinosarcoma is a rare neoplasm; with a poor prognosis. The most common epithelial components are adenocarcinoma or squamous cell carcinoma, whereas the most common mesenchymal components are chondrosarcoma. It should not be confused with the most common carcinoma ex-pleomorphic adenoma, in which the epithelial component alone is malignant. This condition might exhibit with a wide variety of presentation and symptoms along with associated conditions. We present a case of an old patient who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
5
1
Order By: Relevance
“…The median age of patients in our study was 66 years, and 43% of patients were diagnosed between the ages of 50 and 70 years. Some studies report that carcinosarcoma has a predilection to occur in males while others report no sex predominance 14–16 . Our study demonstrated a slightly higher frequency in males (59% vs 41%).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The median age of patients in our study was 66 years, and 43% of patients were diagnosed between the ages of 50 and 70 years. Some studies report that carcinosarcoma has a predilection to occur in males while others report no sex predominance 14–16 . Our study demonstrated a slightly higher frequency in males (59% vs 41%).…”
Section: Discussioncontrasting
confidence: 50%
“…Some studies report that carcinosarcoma has a predilection to occur in males while others report no sex predominance. [14][15][16] Our study demonstrated a slightly higher frequency in males (59% vs 41%). The most common reported site of involvement for carcinosarcoma is the parotid gland (65%), followed by submandibular glands (19%).…”
Section: Discussionmentioning
confidence: 42%
“…The sarcomatous areas had a higher mean fractional allelic loss as compared to the carcinomatous areas suggesting additional mutations in those areas [13]. Katsakhyan et al reported a case of carcinosarcoma harboring PLAG1 translocation with an adjacent PA with an HMGA2 translocation [15]. As these translocations are mutually exclusive, it was concluded that the carcinosarcoma most likely came from another PA with PLAG1 mutation or originated de novo, thereby suggesting that the presence of PA is not conclusive of carcinosarcoma ex pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In general, radical surgical exploration coupled with high dosage chemotherapy coupled with radiation are necessary for treatment. However, even with this aggressive regimen disease reoccurs in about 66% of patients, with metastatic dissemination in about 50% 8,9 (Table 1). Interestingly, the lungs seem to be the most common site of dissemination, but this was not seen in the present case.…”
Section: Discussionmentioning
confidence: 99%